‘FACE TO FACE WITH SCIENTISTS’ IN BRAZIL’S SEMI-ARID COAST: WHAT DO STUDENTS’ MENTAL MAPS REVEAL ABOUT MANGROVES AND ESTUARIES? - Leite, Letícia Borges; Barroso, Hortência de Sousa; Garcia, Tatiane Martins; Soares, Marcelo Oliveira; Leal, Ana Catarina Barboza; Costa, Maria Eduarda Andrade; Matos, Fábio de Oliveira; Mota, Erika Freitas (Geosaberes; Vol 16 (2025), 2025)
We tested the hypothesis that participation in the “Face to Face with Scientists” initiative enhances students’ environmental perception, leading to an increase in the occurrence of signs related to mangroves and estuaries in their mental maps. To test this, each student created an initial mental map based on their prior knowledge of mangroves and estuaries, a second map after the first activity with scientists from the PELD CSB project, and a final one after the field class along the Ecological Trail of the Pacoti River Estuary. The mental maps were analyzed through classification and quantification of signs and underwent interpretive analysis. Our hypothesis was confirmed; however, perceptions of the relationship between humans and the environment remained scarce even after the activities, indicating a strong resistance to transforming the dualistic view of humans and nature.